Stability of Risk Perception Across Pandemic and Non-pandemic Situations Among Young Adults: Evaluating the Impact of Individual Differences - Buelow, Melissa T.; Kowalsky, Jennifer M.; Brunell, Amy B. (Frontiers in Psychology, 2022)
Previous research suggests a higher perceived risk associated with a risky behavior predicts a lower likelihood of involvement in that behavior; however, this relationship can vary based on personality characteristics such as impulsivity and behavioral activation. During the COVID-19 pandemic, individuals began to re-evaluate the level of risk associated with everyday behaviors. But what about risks associated with “typical” risk-taking behaviors? In the present study, 248 undergraduate student participants completed measures of impulsivity, behavioral activation and inhibition, propensity to take risks, numeracy, and perceptions of and involvement in both risk-taking behavior and health promoting behavior (e.g., blood donation, registering as an organ donor, vaccination). Our study revealed that higher behavioral inhibition and greater propensity to take risks predicted greater likelihood of involvement in COVID-19-related risk behaviors, even after accounting for perceived risks and benefits of the behavior. Greater likelihood of involvement in social risk behaviors was predicted by greater numeracy and risk-taking propensity. A greater propensity to take risks and greater impulsivity predicted increased health/safety risk behaviors. For the likelihood of registering to become an organ donor, increasing risk perception, both before and during the pandemic, was associated with greater likelihood of registering, but greater risk-taking propensity was associated with a decreased likelihood of organ donation registration. For flu vaccination, a greater propensity to take risks was associated with a greater likelihood of flu vaccination during the 2020-2021 flu season. Both cognitive and personality factors can predict involvement in risk-taking and health-promotion behaviors, warranting their continued examination.